Efektivitas Teknik Modeling Dan Self Management Terhadap Self-Affiliation Ditinjau Dari Jenis Kelamin Siswa - Petrisia Anas Waluwandja; Yenssy Marvilen Fanggidae (JURKAM: Jurnal Konseling Andi Matappa, 2019)
This research aims to determine the difference of self-times students of grade X SMA Swasta PGRI Kupang based on modeling and self-management techniques, gender, and interaction of modeling and self-management techniques with gender in Student's self-affiliation needs. The research method used is the Quasi-experiment with the two-factor design research plan or often called 2 X 2 factorial design. The population of this study is all students of grade X private school SMA PGRI Kupang, which amounted to 423 students, with samples of 100 students. Every single group consists of 25 students where each group is divided into male and female groups. Sampling techniques using simple random sampling. The results showed that: (1) There is no difference of self-affiliation students of grade X  SMA Swasta PGRI Kupang based on modeling and self management techniques; (2) There is no difference of self-affiliated students of grade X SMA Swasta PGRI Kupang based on students' gender; and (3) No interaction of modeling and self-management techniques with the gender of students in determining the need of self-affiliated students of grade X SMA Swasta PGRI Kupang.